A label-free, electrochemical SERS-based assay for detection of DNA hybridization and discrimination of mutations. - Johnson, R; Richardson, J; Brown, T; Bartlett, P (2012)
A label-free, surface-enhanced Raman spectroscopy-based assay for detecting DNA hybridization at an electrode surface and for distinguishing between mutations in DNA is demonstrated. Surface-immobilized DNA is exposed to a binding agent that is selective for dsDNA and acts as a reporter molecule. Upon application of a negative potential, the dsDNA denatures into its constituent strands, and the changes in the spectra of the reporter molecule are monitored. This method has been used to distinguish between a wild-type, 1653C/T single-point mutation and ΔF508 triplet deletion in the CFTR gene. The use of dsDNA-selective binding agents as reporter molecules in a discrimination assay removes the burden of synthetically modifying the target to be detected, while retaining flexibility in the choice of the reporter molecule.